Comparison of Almond Oil Plus Phenol and Sodium Tetradecyl Sulfate for Rectal Prolapse in Children - Tasneem Hafeez Alvi, Samreen Jamil, Nadeem Yaqoob, Muhamamd Zubair, Muhammad Zulqurnain (Pakistan Journal of Medical & Health Sciences, 2023)
Rectal prolapse in children should be treated as a medical emergency, therefore parents and carers should speak with a doctor about the best course of action. Additionally, it’s critical to keep an eye out for any indicators of difficulties in the child, such as bleeding, infection, or faecal incontinence, and to seek medical help right. Methods and Material: One hundred patients were enrolled in the trial and were split evenly between two groups. Patients in cases were administered Phenol in Almond Oil at a 5% concentration, whereas those in control were given Sodium Tetradecyl Sulfate. Both groups were monitored for recurrence and complications on the first post-operative day and during the first post-operative month. Results: Children in cases had a mean age of 5.633.34 years, whereas those in control had a mean age of 7.162.80 years. There were 46 kids in cases and 39 kids in control. There was a statistically significant (P 0.05) correlation between treatment groups and decrease on day one after surgery. After the first postoperative day, 5 children in cases and 1 kid in control experienced bleeding PR. A post-POD increase in bleeding PR was not significantly different across treatment groups (P > 0.05). At the one-month follow-up, 49 of the children in cases and 44 of those in control showed signs of improvement. The proportion of patients in cases who saw their symptoms improve was significantly higher than that of individuals in control (P 0.05). Conclusion: In the treatment of rectal prolepses, we have come to the conclusion that phenol almond oil with a concentration of 5% is more efficient than sodium tetradecyl sulphate. In other words, the post-operative decline was 98% rather than 88% following the first month of follow-up care. Keywords: Rectal Prolapse in children, almond oil plus phenol, sodium tetradecyl, bleeding, recurrence